2023
DOI: 10.1371/journal.pntd.0011047
|View full text |Cite
|
Sign up to set email alerts
|

Assessing dengue fever risk in Costa Rica by using climate variables and machine learning techniques

Abstract: Dengue fever is a vector-borne disease affecting millions yearly, mostly in tropical and subtropical countries. Driven mainly by social and environmental factors, dengue incidence and geographical expansion have increased in recent decades. Therefore, understanding how climate variables drive dengue outbreaks is challenging and a problem of interest for decision-makers that could aid in improving surveillance and resource allocation. Here, we explore the effect of climate variables on relative dengue risk in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Additional research demonstrates that incorporating the same climatic variables analyzed in our study to predict relative risk areas for dengue outbreaks in all cantons may result in model projections failing in certain locations. This observation, as demonstrated by [57][58][59], emphasizes the significance of comprehending the local correlations between dengue cases and external factors such as climate and socioeconomic drivers. Such understanding can lead to improved predictions of dengue locally, enabling better-informed decision-making regarding interventions and resource allocation.…”
Section: Environmental Variablesmentioning
confidence: 81%
“…Additional research demonstrates that incorporating the same climatic variables analyzed in our study to predict relative risk areas for dengue outbreaks in all cantons may result in model projections failing in certain locations. This observation, as demonstrated by [57][58][59], emphasizes the significance of comprehending the local correlations between dengue cases and external factors such as climate and socioeconomic drivers. Such understanding can lead to improved predictions of dengue locally, enabling better-informed decision-making regarding interventions and resource allocation.…”
Section: Environmental Variablesmentioning
confidence: 81%
“…However, extreme climatic conditions were the leading cause of the unprecedented KC outbreaks in 2014 and 2015 [17]. Interannual variations in dengue transmission driven by temperatures, rainfall, relative humidity, or regional climate phenomena, such as ENSO and IOD, have been discussed elsewhere [9,11,14,38,39]. Moreover, suitability analyses have demonstrated critical associations between vector ecology, virus propagation, and climatic variations [15,25,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [27,40] have shown that these climatic covariates are essential to predict dengue incidence. To begin the calibration, a training period is chosen to fit the model 1 using different combinations of covariates and spatio-temporal configurations of the model.…”
Section: Model Selection and Predictionmentioning
confidence: 99%
“…where U t and L t are the upper and lower limits of the prediction interval, respectively, the latter metric is more complete in evaluating the models' predictive capacity when the uncertainty is summarized through a predictive interval [42]. It has been used in previous predictive studies on dengue fever in Costa Rica (see [26,40]). We use the normalized version of RMSE and IS because we can compare different locations regardless of the scale of their relative risk.…”
Section: Model Selection and Predictionmentioning
confidence: 99%